2013
DOI: 10.3329/bjog.v26i1.13758
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Renal Function in Eclampsia

Abstract: Objective: Aim of the study is to identify changes that occur in renal function in eclampsia patients and to determine the effect of impaired renal function on pregnancy outcome Materials and Methods: This cross-sectional study on the impairment of renal function in eclamptic patients was carried out in the Eclampsia ward of Dhaka Medical College Hospital from July 2009 to December 2009. Study group comprised of 50 diagnosed cases of eclampsia and 50 patients with uncomplicated pregnancy was taken as control. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Another study Khan et al have shown unilateral salpingectomy in 71% cases, unilateral salpingoophorectomy in 2% cases, unilateral salpingectomy with other sided tubectomy in 24.66% cases, salpingostomy done in 4 cases, removal of abdominal pregnancy in 4 cases and resection of rudimentary horn in 3 cases. 11 Several observational studies suggested that expectant management was highly successful in women with ectopic pregnancy who presented with very low HCG values. Most clinicians, however, still consider that all ectopic pregnancies need some form of treatment, and few data exist to compare expectant with medical or surgical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Another study Khan et al have shown unilateral salpingectomy in 71% cases, unilateral salpingoophorectomy in 2% cases, unilateral salpingectomy with other sided tubectomy in 24.66% cases, salpingostomy done in 4 cases, removal of abdominal pregnancy in 4 cases and resection of rudimentary horn in 3 cases. 11 Several observational studies suggested that expectant management was highly successful in women with ectopic pregnancy who presented with very low HCG values. Most clinicians, however, still consider that all ectopic pregnancies need some form of treatment, and few data exist to compare expectant with medical or surgical treatment.…”
Section: Discussionmentioning
confidence: 99%